2003
DOI: 10.1097/00126334-200310010-00007
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an Educational Program on Efficacy and Adherence With a Twice-Daily Lamivudine/Zidovudine/Abacavir Regimen in Underrepresented HIV-Infected Patients

Abstract: A 24-week open-label clinical trial was conducted in 195 HIV-infected adults commonly underrepresented in research (35% female, 71% African American, 21% Hispanic, and 20% injection drug users [IDUs]) to evaluate the effect of an HIV educational program on efficacy and adherence with a simple, compact, twice-daily triple nucleoside regimen containing a lamivudine (150 mg)/zidovudine (300 mg) combination (COM) tablet plus abacavir (ABC), 300 mg. At baseline, the patients' median plasma HIV-1 RNA level was 4.18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(29 citation statements)
references
References 18 publications
1
27
0
1
Order By: Relevance
“…In the present study the mean adherence to lopinavir/ritonavir over 24 weeks, as measured by MEMS monitors, was 72.8%. This value is well below the 95% adherence target for HAART recipients but is similar to the rates of electronically measured adherence reported by other investigators (Bangsberg et al, 2000;Rawlings et al, 2003). In our cohort of urban HIV clinic patients, factors independently associated with nonadherence were lower CD4+ lymphocyte quartile at study enrollment, lower level of educational attainment, and current cigarette smoking.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In the present study the mean adherence to lopinavir/ritonavir over 24 weeks, as measured by MEMS monitors, was 72.8%. This value is well below the 95% adherence target for HAART recipients but is similar to the rates of electronically measured adherence reported by other investigators (Bangsberg et al, 2000;Rawlings et al, 2003). In our cohort of urban HIV clinic patients, factors independently associated with nonadherence were lower CD4+ lymphocyte quartile at study enrollment, lower level of educational attainment, and current cigarette smoking.…”
Section: Discussionsupporting
confidence: 87%
“…Although illicit drug and alcohol use are commonly analyzed factors in studies of antiretroviral adherence, cigarette smoking is not. None of the major studies that used electronic measurement of antiretroviral adherence listed cigarette smoking among their analyzed variables (Arnsten et al, 2001;Arnsten et al, 2002;Bangsberg, 2006;Bangsberg et al, 2000;Berg et al, 2004;Gross, Bilker, Friedman, & Strom, 2001;Howard et al, 2002;Liu et al, 2001;Paterson et al, 2000;Rawlings et al, 2003). Fogarty et al (2002) published a comprehensive review of more than 200 factors evaluated for association with antiretroviral adherence in the extant literature, and cigarette smoking was not among them.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Because such monitoring is expensive and the bottle cap monitors are cumbersome, the typical study employing MEMS caps is short in duration; generally 24 weeks for antiretroviral research. [3][4][5][6] The need for ART is, however, long term. Little is known about the predictive value of MEMS cap-derived adherence rates at 1 time point for adherence rates at future time points.…”
Section: Discussionmentioning
confidence: 99%
“…Electronic monitoring of adherence, using bottle cap monitors, is a rigorous method of quantifying adherence, and studies conducted using these devices have been influential in understanding the adherence-virologic outcome relationship. [1][2][3] Many of the studies exploring this relationship have been limited to 24 weeks of observation, [3][4][5][6] whereas the need for ART adherence is long term. It would be useful to know whether a quantitative assessment of adherence to ART at 1 time point is predictive of adherence rates in the future.…”
Section: Introductionmentioning
confidence: 99%
“…There is limited evidence about the effectiveness of these interventions from randomized trials (Fairley et al, 2003;Goujard et al, 2003;Pradier et al, 2003;Rawlings et al, 2003;Simoni et al, 2003;Weber et al, 2004). Nevertheless, mathematical modelling studies have shown that even adherence interventions with moderate efficacy can meet generally accepted cost-effectiveness criteria.…”
mentioning
confidence: 99%